Rancangan Area Serapan Air Pada Pemodelan Potensial Listrik Topografi Landai - Delia Meldra (Universitas Putera Batam, 2018)
Measure natural electric voltage at surface used Self-Potential method. Self-Potential one of the methods used to look at subsurface water flow. The negative or positive sign of potential is an important factor for the interpretation of Self-potential anomalies. The finite element technique is applied to model the velocity of water flow, current source, and potential value distribution in the form of 2-D profile. Finite element technique was chosen to solve the problem of boundary conditions and differential equations for Self-Potential modeling. Modeling current sources are obtained by intermediate gradient operation and water flow velocity . From the result of modeling, we get the value of water flow velocity between 10-6 - 10-4 m/s, current source, potential distribution, and potential response on the topography of the slope. Each topography produced different potential response forms, due to the electrokinetic effect. The water flow in the area with slopes topography often causes inundation due to inadequate absorption area, thus causing the grinding of the soil and destroying the road. From the results of this modeling is designed a good water absorption area using visio.